Association Between Body Mass Index and Serum Urea Levels Among Women of Reproductive Age in Waihaong Village, Maluku, Indonesia - Syah Mutiara; Mutmainnah Abbas; Firensca Pattiasina; Filda Vionita Irene de Lima (Journal of Public Health Sciences, 2026)
Chronic kidney disease (CKD) is a growing global health concern, highlighting the importance of identifying modifiable risk factors that affect renal function. Nutritional status, commonly reflected by Body Mass Index (BMI), is one such factor, while serum urea serves as a key biomarker of kidney function. This study examined the relationship between BMI and serum urea levels among women of reproductive age in Waihaong Village. Using a cross-sectional analytical design, 75 participants were selected through purposive sampling. Data collection included informed consent, 10–12 hours fasting, BMI measurement, venous blood sampling, and serum urea analysis. Data were processed with SPSS using the Spearman correlation and multiple regression tests. Results revealed a significant positive correlation between BMI and serum urea levels (r = 0.259, p = 0.025). The median serum urea concentration was 18.3 mg/dL (range: 12.8–37.4 mg/dL), remaining within normal limits. The Kruskal–Wallis test showed no significant difference among BMI categories (χ² = 7.792, p = 0.100), although mean rank values indicated a trend of increasing urea with higher BMI. Multiple linear regression indicated that BMI significantly influenced serum urea (β = 1.045, p = 0.031) after adjusting for diet and physical activity, while other variables showed no significant associations (p > 0.05). The model’s stability was confirmed (VIF < 2). In conclusion, higher BMI is associated with increased serum urea levels, suggesting the need for routine BMI screening to help detect early kidney dysfunction in women of reproductive age.